(3GdfLOjGJ aj GdfSHs - (3CHhGdeXaQ eMeO Hf CMeO Hf eMeO Hf eYGhjI GdCUZQ GdCehj GdCHjhQOj,J (B557 (3g` s ((3eMeO Hf fUQ GdOjf eSYhO GdOGeZGfi s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg Ndjdi Ef GdMK eG JYQaGfg adG TcQ Ef GdMfjf ef GdhLO s
(3BNQgG (B:s
(3Rfi Gdbhe MJi JYQai YfOhRfge EPG QaY GdejRGf cja Cejd JeJ GdfLOjGJ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B209s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1930s
Keywords: (3GdCOHs